Sprachatlas des Dolomitenladinischen und angrenzender Gebiete Band 3 - Goebl, Hans (Editions de Linguistique et de Philologie, 2012)
The third volume contains 215 dialect maps which embrace dialectal terminologies from the furniture to the numerals.Third map volume of a linguistic atlas with five map volumes and two index volumes.